2022
DOI: 10.1080/19490976.2022.2112882
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal TLR4 deletion exacerbates acute pancreatitis through gut microbiota dysbiosis and Paneth cells deficiency

Abstract: Toll-like receptor 4 (TLR4) has been identified as a potentially promising therapeutic target in acute pancreatitis (AP). However, the role of intestinal TLR4 in AP and AP-associated gut injury remains unclear. This study aimed to explore the relationship between intestinal TLR4 and gut microbiota during AP. A mouse AP model was establish by intraperitoneal injection of L-arginine. Pancreatic injury and intestinal barrier function were evaluated in wild-type and intestinal epithelial TLR4 knockout (TLR4ΔIEC) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
(52 reference statements)
2
20
0
Order By: Relevance
“…Results showed that Cryptosporidium infection increased the alpha diversity index of Shannon (p<0.01) and Simpson (p<0.01) (Figure 1B), which demonstrated the increased microbiota complexity of infected animals. The current results are in line with our previous results found in Cryptosporidium-infected horses (Wang et al, 2022). Beta diversity analysis through NMDS, PCoA, Qiime 2b, and PCA analysis revealed microbiota differences between healthy and infected yaks (Figure 3), which were confirmed by comparing the dominating gut microbiota in different taxa (Figures 2, 4).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results showed that Cryptosporidium infection increased the alpha diversity index of Shannon (p<0.01) and Simpson (p<0.01) (Figure 1B), which demonstrated the increased microbiota complexity of infected animals. The current results are in line with our previous results found in Cryptosporidium-infected horses (Wang et al, 2022). Beta diversity analysis through NMDS, PCoA, Qiime 2b, and PCA analysis revealed microbiota differences between healthy and infected yaks (Figure 3), which were confirmed by comparing the dominating gut microbiota in different taxa (Figures 2, 4).…”
Section: Discussionsupporting
confidence: 92%
“…Then we explored the significantly different bacteria between the H and INF groups through DESeq 2 volcano diagram and LEfSe chart analysis. The results showed that a total of 11 phyla and 58 genera were significantly different (Figure 5), which is in accordance with the previously reported results in a study conducted on infected people and horses (Chappell et al, 2016;Wang et al, 2022). The increased genera in yaks were in line with previous studies that found a higher abundance of Desulfovibrio and Butyrivibrio in colitis patients (Berry and Reinisch, 2013;Gryaznova et al, 2021), Prevotellaceae_Prevotella in diarrheic pigs (Yang et al, 2017), Anaerovorax in slow growth performers in nursery pigs (Zhai et al, 2020), Succiniclasticum in LPS induced dual-flow continuous culture system (Dai et al, 2019), Pseudobutyrivibrio in chronic kidney people (Wu et al, 2020), Anaerorhabdus in pulmonary fibrosis persons (Tong et al, 2019), Selenomonas in gastric cancer patients (Zhang et al, 2021), Anaerostipes in diabetic nephropathy patients (Du et al, 2021), Pyramidobacter in endoscopic sphincterotomy surgery gallstone patients (Shen et al, 2021), and Anaerofustis in Alzheimer people (Hou et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gut microbiota disorder aggravates intestinal injury. and the two promote each other's deterioration ( 26 , 27 ). Although chemotherapeutic drugs, such as 5-FU, CPT-11 and L-OHP, can induce intestinal injury ( 28 ), studies have yet to compare the differences between the intestinal injury degree and gut microbiota disorder pattern among them, which form the FOLFIRI (folinic acid, 5-FU, and CPT-11) and FOLFOX colorectal cancer chemotherapy regimens ( 29 ).…”
Section: Discussionmentioning
confidence: 99%